Emergence of Lyme Disease on the French Riviera, a Retrospective Survey - Sevestre, Jacques; Benichou, Antoine; Rio, Vanessa; Delaunay, Pascal; Gonfrier, Géraldine; Martaresche, Cécile; Carlo, Virginie; Nakam, Sarah; Mondain, Véronique; Carles, Michel; Jeandel, Pierre Yves; Durant, Jacques (Frontiers in Medicine, 2022)
(1) Background: The French Riviera has been declared free of Lyme Borreliosis (LB) for years. Many patients are referred for presumed LB, sometimes with atypical clinical signs and/or doubtful serology, calling the diagnosis into question. (2) Methods: Patients were assessed for LB diagnosis, depending on clinical presentation, laboratory findings, and further examination by other medical professionals. (3) Results: Among 255 patients, 45 (18%) were classified as confirmed LB cases (including 28 ongoing LB (10%) and 17 past LB (8%)), and for 210 (82%) a Lyme borreliosis diagnosis was ruled out. Among ongoing LB, 56% had been exposed to or bitten by ticks, exclusively in rural locations of the Alpes-Maritimes. As a result of the diagnostic procedure, 132 (52%) patients had been treated. An alternative diagnosis was established for 134 (52%) patients, covering a wide range of conditions, including mainly psychological (28%) and neurological conditions (25%) or inflammatory and systemic diseases (22%). (4) Conclusions: Our results strongly suggest the endemicity of LB in the Alpes-Maritimes region. Confirmed LB accounted for 18% of patients while 52% were diagnosed with other conditions.